Returns to Controlling a Neglected Tropical Disease: Schistosomiasis Control Programme and Education Outcomes in Nigeria. (11th April 2018) - Makamu, Francis; Azam, Mehtabul; Kazianga, Harounan
Abstract: Using the rollout of the schistosomiasis campaign in Nigeria as a quasi-experiment, we examine the impact of the disease control programme on school-age children education outcomes. Schistosomiasis is a parasitic disease caused by infections from a small worm. Its most severe effects hamper growth and cognitive development of children. The mass campaign targeted four states that saw large reduction in the infectious disease afterwards. Using difference-in-differences strategy, we find that the cohort exposed to the treatment in rural areas accumulated an additional 0.6 years of education compared to cohort not exposed to the treatment. Moreover, the impact of the schistosomiasis treatment is mainly on girls residing in rural areas.